A qualitative process evaluation of a nasal spray intervention to prevent respiratory tract infections - Amelia Dennis; Judith Joseph; Kate Greenwell; Sascha Miller; Jane Vennik; Laura Dennison; Sian Holt; Katherine Bradbury; Adam W. A. Geraghty; Paul Little; Lucy Yardley (PLoS ONE, 2025)
Nasal sprays could be used to prevent and manage respiratory tract infections (RTIs). As part of a randomized controlled trial (ISRCTN17936080), participants received one of two nasal sprays (gel-based vs. saline) and a digital intervention. The digital intervention used behaviour change theories to encourage nasal spray use to reduce the severity and occurrences of RTIs. We explored participants’ experiences of the digital intervention and nasal spray. We interviewed 31 participants (aged 19–80), sampled from the two nasal spray intervention trial arms across 3 winter seasons (including at the height of COVID-19). We analysed the interviews using thematic analysis and found two themes regarding facilitators and barriers to nasal spray use. The facilitators of nasal spray use revolved around belief in nasal spray efficacy for infection, belief the nasal spray is safe, motivation to avoid infection, sense of control over infection, and how the nasal spray is integrated into lifestyle. Barriers to nasal spray use included the belief the nasal spray is ineffective, belief the nasal spray is unnecessary, and usage difficulties. Overall, the results highlight the role of beliefs, lifestyle integration, and usage difficulties in nasal spray adherence, with implications for future digital interventions, such as addressing concerns about the nasal spray being perceived as medication.